Determinants of Male Involvement in Family Planning Services in Tarime District, Tanzania - Machinda, Zena; Mbonile, Milline; Mtae, Harrieth (Tanzania Journal for Population studies and Development, 2020)
This paper examines the determinants of male involvement in family planning services by investigating the relationship between knowledge and male involvement in family planning, and between the involvements of both sexes in family planning services. The study adapted a mixed research design whereby quantitative and qualitative approaches were employed to generate primary data, complemented by other methods like in-depth interviews, focus group discussions and documentary review. The main tool of data collection was a questionnaire, and data analysis was done using descriptive statistics, logistic regression; while qualitative data were subjected to content analysis. The unit of analysis was the individual at household level, and questionnaires were served to 312 households, while in-depth interviews involved 12 key informants. The major findings indicated that many people were currently not practicing family planning methods (73.1% for females and 47.2% for males) although the knowledge about family planning was high (94.6% for females, and 96.0% for males). Some of the reasons for not using family planning were fear of side-effects like having deformed children, fear of cancer, heavy pain during delivery and wives being unfaithful for they have protections. The ANOVA findings showed that there is statistically significant relationship between knowledge of males and use of family planning in future, at p=0.013. The study recommends an improvement in the awareness of family planning services, and allowing more innovative strategies like SMS communication especially in rural areas. Equally, more qualified staff at all levels should be employed to bridge the gap between service providers and clients, which is a major concern.